2022
DOI: 10.48550/arxiv.2201.01583
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust entangling gate for capacitively coupled few-electron singlet-triplet qubits

Guo Xuan Chan,
Xin Wang

Abstract: The search of a sweet spot, locus in qubit parameters where quantum control is first-order insensitive to noises, is key to achieve high-fidelity quantum gates. Efforts to search for such a sweet spot in conventional double-quantum-dot singlet-triplet qubits where each dot hosts one electron ("two-electron singlet-triplet qubit"), especially for two-qubit operations, have been unsuccessful. Here we consider singlet-triplet qubits allowing each dot to host more than one electron, with a total of four electrons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…It has also been observed in a similar system that the sign of the exchange energy may reverse, removing a long-standing constraint for the construction of dynamically corrected exchange gates [37]. On the theory side, calculations based on the Configuration Interaction (CI) techniques on few-electron multi-quantum-dot systems have demonstrated negative exchange interactions and their implication on robust quantum control [43][44][45]. Other studies on these systems have unveiled their potentials for tunable couplings [30], robust quantum gates [41], as well as other interesting properties [42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been observed in a similar system that the sign of the exchange energy may reverse, removing a long-standing constraint for the construction of dynamically corrected exchange gates [37]. On the theory side, calculations based on the Configuration Interaction (CI) techniques on few-electron multi-quantum-dot systems have demonstrated negative exchange interactions and their implication on robust quantum control [43][44][45]. Other studies on these systems have unveiled their potentials for tunable couplings [30], robust quantum gates [41], as well as other interesting properties [42].…”
Section: Introductionmentioning
confidence: 99%
“…In double quantum dots (DQD) hosting two electrons, it has been shown that the deformation potential and piezoelectric interaction play major roles in the electron-phonon dephasing, and all channels of phonon couplings reduce as the dot distance increases [48,49]. It is an interesting open question how the behavior of the electron-phonon dephasing may change as the number of electrons in the DQD is increased [45].…”
Section: Introductionmentioning
confidence: 99%